Becoming Applied: The Transformation of Economics after 1970 - Roger E. Backhouse; Beatrice Cherrier (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Abstract: This paper conjectures that economics has changed profoundly since the 1970s and that these changes involve a new understanding of the relationship between theoretical and applied work. Drawing on an analysis of John Bates Clark medal winners, it is suggested that the discipline became more applied, applied work be ing accorded a higher st atus in relation to pure theory than was previously the case. Discussing new types of applied work, the changing context of applied work, and new sites for applied work, the paper outlines a research agenda that will test the conjecture that there has been a changed understanding of the nature of applied work and hence of economics itself.
Keywords: A10; B20; B40; C00; 330; Applied economics; theory; Clark Medal; JEL codes; core; policy; computation; data; econometrics